Раскопки в портовой части средневековой Сугдеи в 2009 г. - Майко, В.В.; Джанов, А.В.; Фарбей, А.М. (Археологічні дослідження в Україні, 2010)
Results of excavations at the port part of Sugdea which were the continuation of the works from 2006 to 2008 are published. For the first time the largest area of building-up was fully studied, periods of its construction and peculiarities of material culture from the second half of the 10th c. to the beginning of the 16th c. were determined.